Reformulating Compensation Payment Norms In Land Acquistion For Public Interest - Pebriandi Millenium Saragi; I Nyoman Nurjaya; Herlindah Herlindah (International Journal of Islamic Education, Research and Multiculturalism, 2025)
Abstrak